VD_FINDINFO Jug / 2011 / 33 vom 7. Februar 2011 - VD Tribunal cantonal (2011)
SÉQUESTRE DES BIENS SE TROUVANT SUR LA PERSONNE, FRAIS JUDICIAIRES | 135 al. 2 CPP (CH), 135 al. 4 let. a CPP (CH), 268 al. 1 let. a CPP (CH), 268 al. 2 CPP (CH), 268 al. 3 CPP (CH), 268 CPP (CH), 422 al. 2 let. a CPP (CH)